Curriculum of traditional medicine for massage based on science and technology in successful health teaching - J Harahap (Pascasarjana Universitas Pendidikan Indonesia, 2021)
Health in the traditional approach becomes a very important thing because it is owned by the culture of the Indonesian people, for that we need a clear curriculum based on technology and science so as to facilitate the public to access and get services in teaching curriculum based on science and technology. Until now, it is still necessary to need a traditional Health curriculum based on health and technology. The question in this study is how to apply the Health-based curriculum of massage conducted with science and technology to achieve success in existing teaching. The method used is to conduct interviews with a media approach and also observation to obtain information about the application of the curriculum in teaching traditional medicine in the order of science and technology. The results of the study found that the application of the curriculum was not maximized and there was still a need for teaching, and also a shared awareness to get a good curriculum in massage teaching on a science and technology basis